Working women’s perceptions toward sexual protections againts sexual harassment at workplace: a case study at banking sector Melaka Tengah / Farah Hazwani Mohd Zulkufli and Siti Norfazilah Moin - Mohd Zulkufli, Farah Hazwani; Moin, Siti Norfazilah (Faculty of Administrative Science and Policy Studies, 2013)
This study is carried out to identify whether there is any relationship between working women’s perceptions and sexual protection against sexual harassment at workplace and the final objective is to identify which sexual protections (the Employment Act 1955, Article 8 of Federal Constitution, the Code of Practice on Prevention and Eradication of Sexual Harassment and Penal Code) influence the most on the working women’s perceptions against sexual harassment at workplace. 123 working women, professional and non-professional from seven (7) different types of banking institution in Melaka Tengah were chosen as samples. Reliability, normality test, descriptive statistic (respondent’s profile), Spearman’s rank-order correlation and multiple regression analysis were used to analyze the data. The data showed that there was a significant relationship between the working women’s perceptions and the Employment Act 1955, Article 8 of Federal Constitution, the Code of Practice on Prevention and Eradication of Sexual Harassment and Penal Code against sexual harassment at workplace. In addition, the multiple regression analysis showed that the Employment Act 1955 had a greater influence than Article 8 of Federal Constitution and other sexual protections upon the perceptions towards sexual protection against sexual harassment at workplace. This is because; most employees in Malaysia are aware and practically govern under the Employment Act 1955. However, the Malaysian Employers Federation (MEF) is unhappy over the amendments to the Employment Act 1955 (Good Times, 2012). The Executive of Malaysian Employers Federation said the definition used in the Act does not adequately cover certain types of scenarios which is “The definition does not include situations where an employee harasses a client in company premises or where the client harasses an employee. This shows that Employment Act 1955 does not comprehensive enough to cover women from being harass. In a nutshell, it can be said that majority women in banking sector in Melaka Tengah are aware for most of sexual protections being studied but the question arise upon the effectiveness of these protections in protecting the employees from being harassed, preserving and restoring the dignity of the employees or the victims and to fairly punish the wrongdoers. In fact, most of sexual protections in Malaysia are not comprehensive enough to tackle the incident of sexual harassment thus the authority is recommended to amend and to improvise the protections.